2018
DOI: 10.3390/catal8120666
|View full text |Cite
|
Sign up to set email alerts
|

AuPd/3DOM TiO2 Catalysts: Good Activity and Stability for the Oxidation of Trichloroethylene

Abstract: Three-dimensionally ordered macroporous (3DOM) TiO2-supported AuPd alloy (xAuyPd/3DOM TiO2 (x = 0.87–0.91 wt%; y = 0.51–1.86)) catalysts for trichloroethylene (TCE) oxidation were prepared using the polymethyl methacrylate-templating and polyvinyl alcohol-protected reduction methods. The as-prepared materials possessed a good-quality 3DOM structure and a surface area of 49–53 m2/g. The noble metal nanoparticles (NPs) with a size of 3–4 nm were uniformly dispersed on the surface of 3DOM TiO2. The 0.91Au0.51Pd/3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In another work, the three-dimensionally ordered macroporous (3DOM) TiO 2 supported Pd−Au (i.e., Pd 1 −Au 1 /3DOM-TiO 2 ) bimetallic catalyst prepared by poly(vinyl alcohol) protection have shown appreciable activity and stability for HDC of TCE. 99 Moreover, the photocatalytic abatement of TCE by Pd−Au BMCs also have been reported by the researchers applying plasmonic material as support for Pd−Au NPs and taking advantage of plasmonic behavior of Au. In 2017, Balint and coworkers reported a Pd−Au/TiO 2 catalyst prepared by an impregnation method for HDC of TCE which energized by solar radiation in mixture of water/methanol solvents.…”
Section: Applications Of Supported Pd−au Bmcs In Organic Synthesismentioning
confidence: 85%
See 2 more Smart Citations
“…In another work, the three-dimensionally ordered macroporous (3DOM) TiO 2 supported Pd−Au (i.e., Pd 1 −Au 1 /3DOM-TiO 2 ) bimetallic catalyst prepared by poly(vinyl alcohol) protection have shown appreciable activity and stability for HDC of TCE. 99 Moreover, the photocatalytic abatement of TCE by Pd−Au BMCs also have been reported by the researchers applying plasmonic material as support for Pd−Au NPs and taking advantage of plasmonic behavior of Au. In 2017, Balint and coworkers reported a Pd−Au/TiO 2 catalyst prepared by an impregnation method for HDC of TCE which energized by solar radiation in mixture of water/methanol solvents.…”
Section: Applications Of Supported Pd−au Bmcs In Organic Synthesismentioning
confidence: 85%
“…Furthermore, a tandem reaction between benzyl alcohol and nitrobenzene catalyzed by Pd–Au/TiO 2 led to formation of imines and secondary amines, and Pd–Au/TiO 2 BMC mounted on polyacrylonitrile and nylon based nanofibrous membranes (PNFM) through electrospinning successfully oxidized 5-HMF to FDCA (Table , entry 13) . In addition to this, the oxidation of cinnamyl alcohol (Table , entry18), benzyl alcohol (Table , entry1–2) , and 1-phenylethanol (Table , entry 19), reduction of 4-nitrophenol (Table , entry 4), acetylene (Table , entry 12–13), , and photocatalytic HDC of TCE , have also been reported with significant enhancements in TON, TOF, and selectivity than the monometallic analogues as well other supports applied for same purpose. After TiO 2 , ceria (CeO 2 ) is the most frequently applied metal support for Pd–Au BMCs preparation because of its affordability, accessibility, acid–base properties, and the ability to bind with a large variety of metals. , Li and co-workers reported CeO 2 supported Pd 1 –Au 1 (wt %) BMC for α-alkylation of ketones with primary alcohols under visible light where unsaturated ketone formation takes place in the absence of visible light irradiation .…”
Section: Types Of Catalytic Supports and Their Effects In Organic Tra...mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the 20 th century, CVOCs has been produced in large quantities worldwide for use as solvents, preservatives, dry cleaning products, degreasing compounds, synthetic resins, and pharmaceuticals (Zhang et al, 2018). The generation of chlorinated hydrocarbons from leaks, spills or improper disposal led to damage large volumes of soil and groundwater in many industrial and urban areas (Dolinová et al, 2017).…”
Section: Sources Of Cvocsmentioning
confidence: 99%
“…Three-dimensionally ordered macroporous TiO 2 -supported AuPd alloy catalysts were used for trichloroethylene (TCE) oxidation. Dai et al [10] showed the high catalytic activity of some of these materials, obtaining a T 90 of 400 • C at a space velocity of 20,000 mL/(g h). They described how the supported alloys had better catalytic stability and moisture resistance than Au-or Pd-supported samples.…”
mentioning
confidence: 99%